THE SOVEREIGNTY OF THE QURAN ACCORDING TO TAHA JABIR AL-ALWANI: AN ANALYTICAL STUDY - Hasballah Thaib, Zamakhsyari bin; Musolin, Mukhamad Hadi; Annisa, Vina (Universitas Dharmawangsa, 2025)
The study aims to elucidate Taha Jabir Al-Alwani's position, a prominent modern scholar, on the governance of the Quran as articulated in his work